The Authority of the Banten Provincial Public Works and Spatial Planning Agency in Providing Supporting Infrastructure for Banten International Stadium - Izzi Hauro; H. E. Rakhmat Jazuli; Ahmad Rayhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The development of the Banten International Stadium (BIS) represents one of the strategic infrastructure projects initiated by the Banten Provincial Government to establish an international-standard sports complex while supporting regional economic and social development. Despite its strategic significance, the provision of supporting infrastructure has not yet achieved optimal performance, particularly regarding accessibility and governance. This study aims to analyze the authority of the Banten Provincial Public Works and Spatial Planning Agency (DPUPR) in providing supporting infrastructure for the Banten International Stadium and to identify the challenges affecting its implementation. The study employed an empirical juridical approach with a descriptive-analytical design using document analysis and semi-structured interviews with the Head Supervisor of the Banten International Stadium and local community members. The findings indicate that DPUPR's authority is legally established under Law Number 23 of 2014 concerning Regional Government and Banten Governor Regulation Number 48 of 2022. However, the implementation of this authority has not fully reflected good governance principles due to limited interagency coordination, insufficient public transparency, and low community participation. The study also identifies five major implementation challenges, namely structural, administrative, technical, social, and regulatory barriers, which collectively reduce the effectiveness of supporting infrastructure development. Strengthening institutional coordination, improving governance quality, optimizing budget allocation, and accelerating infrastructure provision are essential to enhance the sustainable management of the Banten International Stadium.